Novel molecular signatures and potential therapeutics in renal cell carcinomas: Insights from a comparative analysis of subtypes - ARĞA, KAZIM YALÇIN (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
Renal cell carcinomas (RCCs) are among the highest causes of cancer mortality. Although transcriptome profiling studies in the last decade have made significant molecular findings on RCCs, effective diagnosis and treatment strategies have yet to be achieved due to lack of adequate screening and comparative profiling of RCC subtypes. In this study, a comparative analysis was performed on RNA-seq based transcriptome data from each RCC subtype, namely clear cell RCC (KIRC), papillary RCC (KIRP) and kidney chromophobe (KICH), and mutual or subtype-specific reporter biomolecules were identified at RNA, protein, and metabolite levels by the integration of expression profiles with genome-scale biomolecular networks. This approach revealed already-known biomarkers in RCCs as well as novel biomarker candidates and potential therapeutic targets. Our findings also pointed out the incorporation of the molecular mechanisms of KIRC and KIRP, whereas KICH was shown to have distinct molecular signatures. Furthermore, considering the Dipeptidyl Peptidase 4 (DPP4) receptor as a potential therapeutic target specific to KICH, several drug candidates such as ZINC6745464 were identified through virtual screening of ZINC molecules. In this study, we reported valuable data for further experimental and clinical efforts, since the proposed molecules have significant potential for screening and therapeutic purposes in RCCs.
Keywords: Biomarker; Drug repositioning; Kidney; Renal cancers; Transcriptome; Systems biology; EXPRESSION; PROTEIN; BIOMARKERS; NETWORK; CANCER; OVEREXPRESSION; METABOLISM; APOPTOSIS; PROLIFERATION; INTEGRATION